Resolução de problemas como metodologia de ensino : uma análise das repercussões de uma formação continuada - Miranda, Ana Sofia Macedo Szczepaniak (2015)
This study arose from the question of how the participation in a continuing education course on Troubleshooting deflects in a group of teachers who teach mathematics in a public school. It aimed to understand the repercussions that a course of in-service training Troubleshooting as a methodological perspective on teaching practice of these teachers. With specific objectives it was sought to understand how this group of teachers who teach math realize their pedagogical practice in relation to Troubleshooting as a methodological teaching; to analyze how problem solving is used by the group of teachers; to analyze the limits and possibilities to incorporate Troubleshooting as a teaching methodology and understand the changes that a proposed in-service training on Troubleshooting triggers the group of teachers who participated in it. The survey was conducted with eleven teachers of the initial years. The research was qualitative nature of the case study type, and had its data analyzed by Textual Discursive Analysis. From this analysis it was revealed three categories: "The perceptions of the teachers on the teaching and learning before ongoing education", "The analysis of the changes brought in teachers from the ongoing education” ; “In-service training as a possible and necessary practice." In the first category the study revealed that the group perceives weaknesses in the initial training, they have difficulties and insecurities in relation to mathematics teaching and that they work the Troubleshooting in a simple and conventional way. In the second category, it was showed that there were significant changes in the group from the training course service. It was possible to notice an improvement over the mathematical knowledge, as well as Troubleshooting as a methodological teaching and the group acknowledgment of the possibility to incorporate this approach in their practice. The third category presented as results of this study shows that the course of in-service training has enhanced planning and reflection of teaching practice, so being possible and necessary in schools.